Syn-Selective crotylation of aldehydes using bismuth-crotyl bromide-(1-butyl-3-methylimidazolium bromide) combination: some synthetic applications. Issue 17 (13th April 2017) - Goswami, Dibakar; Koli, Mrunesh R.; Chatterjee, Sucheta; Chattopadhyay, Subrata; Sharma, Anubha
Abstract : Highly syn -selective crotylation of aldehydes was achieved using Bi-[bmim][Br]-crotyl bromide combination, leading to an easy, stereodivergent method to synthesise important targets. Abstract : The Bi-[bmim][Br] combination has been found to offer high syn -selectivity in the crotylation of aldehydes with crotyl bromide using practically stoichiometric amounts of the reagents. The room temperature ionic liquid (RTIL), [bmim][Br], activated Bi metal in the presence of oxygen to produce crotylbismuthdibromide, which reacted with the aldehydes at room temperature. The major anti – syn diastereomeric product obtained from the crotylation of ( R )-cyclohexylideneglyceraldehyde was utilized for the synthesis of dictyostatin and cryptophycin segments, and (+)- cis -aerangis lactone, using standard synthetic protocols.